2012
DOI: 10.1111/j.1532-950x.2012.00997.x
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Comparison of a Single‐Layer (Continuous Lembert) versus Two‐Layer (Simple Continuous/Cushing) Hand‐Sewn End‐to‐End Jejunoileal Anastomosis in Normal Equine Small Intestine

Abstract: One-layer jejunoileostomy can be created in a shorter time and maintain a larger anastomosis luminal diameter without compromising maximum bursting pressure when compared to 2-layer jejunoileostomy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

8
37
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 16 publications
(48 citation statements)
references
References 23 publications
8
37
3
Order By: Relevance
“…Evaluation of BS has been the preferred modality to investigate anastomotic integrity and intestinal healing in horses . Several studies have compared BS of jejunojejunal anastomoses in horses using different suture patterns or stapling techniques .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Evaluation of BS has been the preferred modality to investigate anastomotic integrity and intestinal healing in horses . Several studies have compared BS of jejunojejunal anastomoses in horses using different suture patterns or stapling techniques .…”
Section: Discussionmentioning
confidence: 99%
“…Recently, an in vitro study has compared hand‐sewn single‐layer continuous Lembert to double‐layer (simple continuous/Cushing) jejunoileal anastomoses in horses . This study used a model for which anastomotic segments were distended using room air infusion at variable rates between 200 and 590 mL/min.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there have been concerns raised that JI anastomoses may be more prone to obstruction and therefore colic, recent reports of clinical use of JI have not supported this concern (50% JI and 48% JJ) . It is possible that the increase is because of disparity in lumen diameter and muscularity of the ileum and jejunum resulting in an anastomosis that is smaller than the adjacent jejunum as observed ex vivo . Alternatively it could be a result of functional dissimilarity of the jejunum and ileum.…”
Section: Discussionmentioning
confidence: 99%
“…A 2 layer end‐to‐end hand sewn small intestinal anastomosis consisting of a simple continuous technique for the mucosa/submucosa followed by an inverting continuous technique in the seromuscular layer is most commonly performed by equine surgeons . However, recent ex vivo studies have demonstrated that 1 layer techniques are biomechanically equivalent, faster to perform, and may result in anastomoses with larger lumen diameters compared with 2 layer techniques …”
mentioning
confidence: 99%